Between the common and the private space: Tensions in the maintenance of high-rise residential buildings - Natalia Ponce-Arancibia (Íconos, 2023)
The morphological, social, and legal particularities that high-rise residential buildings present require certain collective organizational practices that are necessary for building management and maintenance. This condition reflects tensions and conflicts that eventually lead to an accelerated deterioration and abandonment of the built environment. Sometimes, these conditions manifest themselves in critical episodes, such as the total or partial loss of residential assets triggered by unexpected events, such as the 2017 earthquake in Mexico City. In this sense, this article intends to analyze the practices and social dynamics that hinder the collective appropriation of goods and common domain spaces in the residential environment. The methodological strategy is based on a retrospective analysis of the problem of the appropriation and management of space based on interviews with residents of the Morelos Residential Center (Mexico City). It is concluded that the difficulties expressed in relation to collective organization obey the logic that the neoliberal project has strengthened in the housing field, which, through the hegemony of the tenure system based on individual private property, has permeated forms of social relationship between inhabitants, installing patterns of individuation that shape apathy towards the appropriation of space and common domain goods.